If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 2x(3x + 2x) = 480 Combine like terms: 3x + 2x = 5x 4x + 2x(5x) = 480 Remove parenthesis around (5x) 4x + 2x * 5x = 480 Reorder the terms for easier multiplication: 4x + 2 * 5x * x = 480 Multiply 2 * 5 4x + 10x * x = 480 Multiply x * x 4x + 10x2 = 480 Solving 4x + 10x2 = 480 Solving for variable 'x'. Reorder the terms: -480 + 4x + 10x2 = 480 + -480 Combine like terms: 480 + -480 = 0 -480 + 4x + 10x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-240 + 2x + 5x2) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-240 + 2x + 5x2)' equal to zero and attempt to solve: Simplifying -240 + 2x + 5x2 = 0 Solving -240 + 2x + 5x2 = 0 Begin completing the square. Divide all terms by 5 the coefficient of the squared term: Divide each side by '5'. -48 + 0.4x + x2 = 0 Move the constant term to the right: Add '48' to each side of the equation. -48 + 0.4x + 48 + x2 = 0 + 48 Reorder the terms: -48 + 48 + 0.4x + x2 = 0 + 48 Combine like terms: -48 + 48 = 0 0 + 0.4x + x2 = 0 + 48 0.4x + x2 = 0 + 48 Combine like terms: 0 + 48 = 48 0.4x + x2 = 48 The x term is 0.4x. Take half its coefficient (0.2). Square it (0.04) and add it to both sides. Add '0.04' to each side of the equation. 0.4x + 0.04 + x2 = 48 + 0.04 Reorder the terms: 0.04 + 0.4x + x2 = 48 + 0.04 Combine like terms: 48 + 0.04 = 48.04 0.04 + 0.4x + x2 = 48.04 Factor a perfect square on the left side: (x + 0.2)(x + 0.2) = 48.04 Calculate the square root of the right side: 6.93108938 Break this problem into two subproblems by setting (x + 0.2) equal to 6.93108938 and -6.93108938.Subproblem 1
x + 0.2 = 6.93108938 Simplifying x + 0.2 = 6.93108938 Reorder the terms: 0.2 + x = 6.93108938 Solving 0.2 + x = 6.93108938 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.2' to each side of the equation. 0.2 + -0.2 + x = 6.93108938 + -0.2 Combine like terms: 0.2 + -0.2 = 0.0 0.0 + x = 6.93108938 + -0.2 x = 6.93108938 + -0.2 Combine like terms: 6.93108938 + -0.2 = 6.73108938 x = 6.73108938 Simplifying x = 6.73108938Subproblem 2
x + 0.2 = -6.93108938 Simplifying x + 0.2 = -6.93108938 Reorder the terms: 0.2 + x = -6.93108938 Solving 0.2 + x = -6.93108938 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.2' to each side of the equation. 0.2 + -0.2 + x = -6.93108938 + -0.2 Combine like terms: 0.2 + -0.2 = 0.0 0.0 + x = -6.93108938 + -0.2 x = -6.93108938 + -0.2 Combine like terms: -6.93108938 + -0.2 = -7.13108938 x = -7.13108938 Simplifying x = -7.13108938Solution
The solution to the problem is based on the solutions from the subproblems. x = {6.73108938, -7.13108938}Solution
x = {6.73108938, -7.13108938}
| 69=8c-3 | | 6e-1=11 | | -3t^2-14t+4=0 | | x^2*14x+40=0 | | 8x^2+25x-200=0 | | 20x=192 | | 4x^2+25-200=0 | | ((2x-1)/(x+2))+((x+2)/(2x-1))=(10/3) | | 8x^2-7x=4x-14x^2 | | 0.06/0.02 | | (3x+8)=(9x-4) | | 6x+105=14x-7 | | 119-4x=41x+19 | | 8y+1000/Y=0 | | 2y^2-50y+308=0 | | 135+x=90 | | 8y+1000/Y | | 135+x=180 | | 4/5-2/4 | | -45=-6f(-3f-4) | | -2x+5y+7=0 | | x+40+5x+14+90=180 | | 6/7-2/5 | | 7x+2=13x-3 | | y^2+25y+154=0 | | 4/6-2/9 | | (x-4)(x-4)-25=0 | | 3*2-(2-5)=9 | | 8.3-0.6x=11.3 | | 5x+130=13x-6 | | 11.3-0.6x=11.3 | | 6X+5-8X+15= |